Perancangan Sistem Informasi Peminjaman Dan Pengembalian Buku Perpustakaan Berbasis Web Di Smk Tujuh Lima 1 Purwokerto - Joko Dwi Mulyanto; Windi Apriliyanti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2023)
The school library is part of the education component that cannot be saparated form the school environment. As one form of education, the school library function as a learning support for students as well as fosters interest in reading in order to achieve educational goals at school. The library is an instituttion that manages the collection of written, printed, and or recorded work professionally with a standard system to meet the needs of education, research, presevation, information and recreation of students as the use of the library. Based on the author’s research, SMK Tujuh Lima 1 Purwokerto is an educational institution where there is a library with a manual book-lending service system using a book recording method or it can be said that it has not been computerized, thus hampering lending activities within the library itself, using a computerized system so that it can lighten and facilitate activities in the library in borrowing and returning books. The software development method used is the prototype method. Then made a web-based book lending and return information system design which aims to make it easier for officers to manage library data and can minimize the riskof loss or damage to documents.